Overcoming barriers to climate-smart agriculture in South Asia - Ishtiaque, Asif; Krupnik, Timothy J; Krishna, Vijesh V.; Uddin, Md. Nasir; Aryal, Jeetendra Prakash; Srivastava, Amit Kumar; Kumar, Shalander; Shahzad, Muhammad Faisal; Bhatt, Rajan; Gardezi, Maaz; Bahinipati, Chandra Sekhar; Nazu, Shahnaz Begum; et al. (Nature Publishing Group, 2024)
Despite the promise of climate-smart agriculture (CSA) to improve food security in South Asia, most CSA practices and technologies have not been widely adopted. We identify the key barriers to CSA adoption in South Asia and suggest strategies to overcome them to increase CSA adoption at scale.